Testing of glutathione contents by calcein-Cu(II) fluorescence spectra. (January 2019) - Liu, L; Wu, W; Zhang, Y; Chen, W; Guo, J Y; Li, S Z
Abstract: Glutathione (GSH) is a natural active tripeptide formed by glutamic acid, glycine, and cysteine, which plays a vital role in many physiological processes of the living body. The GSH contents of the sample were detected by using calcein-Cu(II) fluorescence system in our work. In a Na2 HPO4 -NaH2 PO4 buffer with a pH of 8.0, Cu (II) could coordinate with calcein. Calcein-Cu(II) complex was not fluorescent which led to a reduction of calcein fluorescence intensity. For the strong affinity of GSH with copper (II), the addition of GSH solution would make calcein free from calcein-Cu(II) complex and recover fluorescence. Excitation spectra and emission spectra of calcein and calcein-Cu(II) system were researched. And fluorescence spectra of calcein-Cu(II) system with different GSH contents were investigated. The influence of experimental parameters such as reaction time and the addition sequence of the solution on results was also studied. We got the following conclusions: first, Cu(II) can make the calcein fluorescence be quenched, but the wavelength at the peak of fluorescence is unchanged. Second, the addition of Glutathione can make the fluorescence of calcein - Cu (II) system recover. And the change of the fluorescence intensity has a linear relationship with the concentration of GSH in the range from 2 × 10 −6 to 1.0 × 10 −5 mol/l. Third, response time may be extended appropriately for complete reaction in the system. At last, the experimental results have shown that calcein - GSH - Cu(II) system has higher sensitivity and better stability than calcein - Cu(II)- GSH system. This test method is of great importance in practical application.